The Implementation of Justice Value for Consumer Protection Study of the Financial Services Authority Regulation Number: 1/Pojk.07/2013 Concerning Consumer Protection - Dwi Edi Wibowo; Liana Endah Susanti; Aditya Migi Prematura (International Journal of Law Society Services, 2022)
The role of the internet in information technology has been used to develop the financial industry through modification and efficiency of financial services, known as Financial Technology or Fintech.  Fintech has many types, including payment startups, lending, personal finance, retail investment, crowdfunding, remittances, financial research and others. Fintech, a type of technology-based lending and borrowing money or peer to peer lending (P2P-lending), is a type of Fintech that is growing rapidly in Indonesia, problems that must be resolved regarding the Implementation of Justice Value For Consumer Protection (Study of The Financial Services Authority Regulation Number: 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector). This research used normative juridical research method, which is focused on studying the implementation of the rules or norms in positive law, the conclusion of the Financial Services Authority Regulation Number 1/POJK.07/2013 concerning Consumer Protection of the Financial Services Sector in terms of its objective to provide protection to consumers is still not optimal, because the Financial Services Authority does not regulate the time frame for responding to complaints that have been submitted by the Consumers in the regulation